Effect of health education on the management of lower back pain: application of health beliefs model and self-determination theory - Tamulienė, Daiva; Slivovskaja, Ieva; Rakštelienė, Vilma (Slauga. Mokslas ir praktika, 2020)
The number of people suffering from lower back pain is increasing all over the world. This is a serious health problem that may cause disability, absence and increased yearly healthcare costs. The effectiveness of lower back pain treatment is the object of numerous scientific studies. Scientific evidence shows that people’s outlook and motivation to participate in the illness management process can have a significant effect on the management and prognosis of such pain. In the process of preserving and strengthening health, an important role goes to educating the patients, where it is important to not only provide knowledge about the illness but also to encourage the patient’s active participation in pain management. The model of Health Belief reveals a link between these beliefs and behaviour. With this model, a person’s behaviour is usually determined by being aware of a risk to their health, as well as believing in the benefits of preventive actions, confidence in their own ability to take action and personal encouragement to act. A proper environment and support from the loved ones as well as the medical staff have a significant effect on the patient’s behaviour. According to the Theory of self-determination, when the basic psychological needs (for autonomy, competence and relationships) are catered for, the patients’ participation in managing their illness becomes more likely and leads to better results.